Parkinson Disease - Raudah Novita Putri; Intan Sahara Zein (An-Najat, 2023)
Parkinson's disease is a disorder of brain function caused by the degeneration process of the basal ganglia in the substantia nigra pars compacta (SNc) cells and is characterized by characteristics such as tremors at rest, muscle and joint stiffness (rigidity), slowness of movement and speech (bradykinesia) and instability. upright position (postural instability). There is no medicine or treatment that can change Parkinson's Disease. The most effective symptomatic treatment is levodopa, which has better effectiveness on quality of life in Parkinson's Disease than other therapies. Motor fluctuations and dyskinesias later in the course of the disease may be improved with additional treatment. There are 10% of patients per year with intractable motor fluctuations who undergo further therapy, including deep brain stimulation surgery. The importance of multidisciplinary care has been proven to better manage non-motor symptoms in Parkinson's Disease.